Carbon export fluxes and export efficiency in the central Arctic during the record sea‐ice minimum in 2012: a joint 234Th/238U and 210Po/210Pb study. Issue 7 (24th July 2016) - Roca‐Martí, Montserrat; Puigcorbé, Viena; Rutgers van der Loeff, Michiel M.; Katlein, Christian; Fernández‐Méndez, Mar; Peeken, Ilka; Masqué, Pere
Abstract: The Arctic sea‐ice extent reached a record minimum in September 2012. Sea‐ice decline increases the absorption of solar energy in the Arctic Ocean, affecting primary production and the plankton community. How this will modulate the sinking of particulate organic carbon (POC) from the ocean surface remains a key question. We use the 234 Th/ 238 U and 210 Po/ 210 Pb radionuclide pairs to estimate the magnitude of the POC export fluxes in the upper ocean of the central Arctic in summer 2012, covering time scales from weeks to months. The 234 Th/ 238 U proxy reveals that POC fluxes at the base of the euphotic zone were very low (2 ± 2 mmol C m −2 d −1 ) in late summer. Relationships obtained between the 234 Th export fluxes and the phytoplankton community suggest that prasinophytes contributed significantly to the downward fluxes, likely via incorporation into sea‐ice algal aggregates and zooplankton‐derived material. The magnitude of the depletion of 210 Po in the upper water column over the entire study area indicates that particle export fluxes were higher before July/August than later in the season. 210 Po fluxes and 210 Po‐derived POC fluxes correlated positively with sea‐ice concentration, showing that particle sinking was greater under heavy sea‐ice conditions than under partially ice‐covered regions. Although the POC fluxes were low, a large fraction of primary production (>30%) was exported at the base of the euphotic zone in most of the study area during summer 2012, indicating a high export efficiency of the biological pump in the central Arctic. Key Points: First use of 234 Th/ 238 U together with 210 Po/ 210 Pb as proxies for particulate organic carbon export in the Arctic Low particulate organic carbon fluxes escaping from the euphotic zone during the record sea‐ice minimum in 2012 High export efficiency of the biological pump in the central Arctic